Serum angiopoietin-2 as a noninvasive diagnostic marker of stages of liver fibrosis in chronic hepatitis C patients - Mohamed M Makhlouf; Mahmoud A Osman; Shereen A.B. Saleh; Wael A Yousry; Mohamed L Soliman; Wahid H Doss; Fayrouz S Wahba (SpringerOpen, 2016)
Background The process of fibrogenesis is associated with the development of disease-specific markers. The management of chronic hepatitis C (CHC) depends on the staging of liver fibrosis. Use of noninvasive methods is preferable in diagnosis and follow-up. Objective The aim of this study is to evaluate serum angiopoietin-2 (Ang-2) as a noninvasive marker in the diagnosis of different stages of liver fibrosis in CHC patients. Materials and methods A total of 90 individuals were included. They were divided into a patient group (75 patients) and a control group (15 normal individuals). Serum Ang-2 was measured using enzyme-linked immunosorbent assay. Pretreatment liver biopsy was performed for the patients. The METAVIR score was used in the staging of liver fibrosis. A comparison of Ang-2 was performed between patients and controls, and between different stages of liver fibrosis. A receiver operating characteristic curve analysis was carried out to determine the best cutoff values of Ang-2 in the differentiation of different stages of fibrosis. Results Ang-2 serum levels were significantly higher in advanced stages of liver fibrosis. The cutoff points 869.3, 2226, and 7205 pg/ml were the best for differentiating fibrosis stages >F1; >F2; and >F3, respectively. Ang-2, international normalized ratio, α-fetoprotein, and albumin were found to be independent predictors of liver fibrosis using univariate analysis. Conclusion Ang-2 correlated significantly with liver fibrosis stage. It can aid noninvasive differentiation between different stages of liver fibrosis in patients with CHC.